(untitled) (Revista Brasileira de Ciências do Envelhecimento Humano, 2022)
The city of Ulm was selected as one of eight “Cities of the Future” throughout Germany in a nationwide competition organised by the Federal Ministry of Education and Research (BMBF). After an ideas and planning phase, the visions of the first two phases are implemented on site in the third phase. The goal is to develop digital and innovative solutions for a sustainable and liveable city together with the citizens. The Centre for General Scientific Continuing Education (ZAWiW) of the University of Ulm, as a partner for the thematic field of education, focuses on social sustainability and develops various educational and participation formats together with other actors as well as citizens in and around Ulm. Digitalisation now reaches almost all areas of life. At the same time, older people in particular are often excluded from participation opportunities due to a lack of access or skills (digital divide). The aim of the project is to build bridges and enable people to use digital technologies in a self-determined way – because social participation increasingly requires digital participation. Approaches were tested together on how “digitisation from below” can succeed in the city. The “Virtual Neighbourhoods” and the “Digital Mentors” are presented here as examples of programmes that have been sustainably anchored and established in the city thanks to the cooperation of various actors. These projects show that it is above all human encounters that reduce fears, give courage and offer support.